Synthesis of 2,4-dihydroxychalcone Derivatives as Potential Antidepressant Effect - Guan, L.-P.; Zhao, D.-H.; Chang, Y.; Wen, Z.-S.; Tang, L.-M.; Huang, F.-F. (Drug Research, 2013)
In this study, twelve 2,4-dihydroxychalcone derivatives were synthesized and evaluated for antidepressant activities using the forced swimming test (FST). The pharmacological test showed that 6 compounds significantly reduced the immobility times in the FST at a dose of 10 mg/kg, indicative of antidepressant activity. Among the derivatives, compounds designated 3d and 3 h exhibited the best antidepressant activity, with reduced immobility time by 32.05% and 34.33%, respectively. In the 5-hydroxytryptophan-induced head-twitch test and yohimbine-induced mortality test, compounds 3d and 3 h increased head-twitch and increased the mortality rate. The mechanisms of the antidepressant effects of compounds 3d and 3 h may be related with the 5-HTP and NE nervous system.
Keywords: 2,4-dihydroxychalcone derivatives; synthesis; antidepressant activity; 5-Hydroxytryptophan; yohimbine